Koncepcje Czesława Znamierowskiego a podstawowe problemy prawa karnego - Patryas, Wojciech (Wydział Prawa i Administracji UAM, 1987)
The article attempts to determine the views of Cz. Znamierowski in the matters closely connected with the penal law issues. Many conceptions and ideas of that author belong to the area of interests of the said branch of law. For example. he declared himself a proponent of finality, supporting the latter theory by philosophical arguments in a dispute with causality. He set forth the original conception of omnissions as acts, the conception which was concurrent in subject- -matter and time with the one proposed by Władysław Wolter. He was a proponent of one of the versions of conceivable intent (dolus eventualis), supporting it with the philosophical foundation. Some of Cz. Znamierowski's proposals, such as e.g. the conception of derivative quilt, go beyond the Code's solutions. Others are his original contribution to the considerations on the rationality of behaviour, the core of the penal law constructions. Finally, the common feature of his proposals is that they shed new light on the penal law issues. Hence, they are worthy to be remembered.
The conception of Czesław Znamierowski and the basic problems of penal law